2023
DOI: 10.5115/acb.23.008
|View full text |Cite
|
Sign up to set email alerts
|

First extensor compartment morphology and clinical significance: a cadaver series study

Abstract: The first extensor compartment of the wrist is a distinctly variable anatomical area. Anatomical variations in this region contribute to the pathophysiology and treatment failure of de Quervain's disease, which is a kind of tenosynovitis that develops in the first extensor compartment of the wrist. We aim to describe the first extensor compartment morphology, to evaluate the septum frequency, location of the septum, and the number of tendons of abductor pollicis longus (APL) and extensor pollicis brevis muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…We described the common tendon number pattern in the 1st EC as 2 APL and 1 EPB tendon slip, which was in line with several previous studies [ 1 , 34 - 37 , 46 ]. However, certain authors reported different results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We described the common tendon number pattern in the 1st EC as 2 APL and 1 EPB tendon slip, which was in line with several previous studies [ 1 , 34 - 37 , 46 ]. However, certain authors reported different results.…”
Section: Discussionsupporting
confidence: 90%
“…Another injection technique with a high efficacy rate (89%) for cases of septa with two-point injections is one and another over the EPB and APL tendons [ 32 ]. In addition, several studies focused on septal prevalence inside the 1st EC (we listed some of them in Table 5 ) [ 33 - 45 ]. Kulthanan and Chareonwat [ 33 ] investigated septal prevalence in patients with de Quervain compared to cadavers of assumably physiological states.…”
Section: Discussionmentioning
confidence: 99%